Evaluation of the Minitek system for identification of nonfermentative and nonenteric fermentative Gram-negative bacteria. - Chester, V (1980)
The Minitek identification system (MT) was compared with a conventional testing battery for the characterization of 735 isolates which included 57 species and groups of nonfermentative (NF) and nonenteric fermentative (NEF) gram-negative bacteria. The MT correctly identified 585 of 616 NF (94,96%) and 115 of 119 NEF (96.65%) bacteria and 700 of 735 strains (95.24%) overall. A total of 31 NF and NEF (4.22%) bacteria were misidentified, and no identification was determined for four strains (0.69%). All strains of Acinetobacter anitratus, Pseudomonas maltophilia, P. fluroescens, and P. putida and all but one strain of P. aeruginosa were correctly identified. The most frequently misidentified taxa were CDC group Va-1, P. pickettii (Va-2), P. mendocina, and Moraxella urethralis (M-4). Supplemental tests were needed for the complete identification of 214 strains (29.11%). An average of 1.54 supplemental tests were used with each of these strains. A total of 134 strains (18.23%) had their identification delayed by 1 day due to supplemental testing. We recommend the use of the 42 degree C growth test with the MT. When used in accord with the manufacturer's instructions and with the MT code book the MT was found to be a valuable system for the identification of a wide variety of common and infrequently encountered NF and NEF bacteria.